A Multi-Scale Diffusion Method for Chromatic Adaptation and Halo Artifact Suppression - Sifuentes, Fabián Concha; Cahuina, Edward Cayllahua; Colque, Rensso Mora (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2025)
Color blindness affects a significant portion of the population, it impacts the visual experience of affected individuals, making chromatic adaptation in digital content crucial for visual accessibility. Existing chromatic adaptation methods effectively improve visual perception but suffer from high computational costs and can produce unwanted halo artifacts. This paper proposes an efficient chromatic adaptation algorithm based on a multi-scale Gaussian pyramid strategy combined with local anisotropic diffusion, effectively eliminating halo artifacts while preserving image quality. Experimental results evaluated with PSNR, local SSIM, MSE, CIEDE2000 and Absolute Difference Maps demonstrate that the proposed method achieves visual quality comparable to state-of-the-art algorithms while drastically reducing processing times by over 90%. Thus, the proposed approach provides an efficient solution, enabling practical integration into iterative applications to enhance visual accessibility for colorblind users.